IJCM_217A: Literacy for health: Bridging the gap between female literacy and health seeking behaviour - Kumari Shivangi; Mehnaz Saira; Abedi Ali Jafar; Ansar M. Athar; Ahmad Sameena (Wolters Kluwer Medknow Publications, 2024)
Background: The private sector has maintained its dominance in the healthcare industry despite numerous government measures to improve public services. Public sector is still not a choice for treatment, various reasons being large distance from residence, poor quality of care, shortage of drugs, poor attitude of health care provider. Enumeration of the factors that defines pattern of the utilization of health services become utmost important. Hence, this study is being conducted to understand the factors behind the utilization of government health services. Objectives: i)To find the prevalence of Reproductive Tract Infections, among married women of reproductive age group, seeking treatment among rural and peri-urban areas of Aligarh. ii) To find the determinants of utilization of reproductive health services among married women in Aligarh. Methods: This cross-sectional study was conducted between 2020-2021 Data was collected through a pretested, semi-structured questionnaire through simple random sampling from 500 married women of reproductive age group, in the field areas registered under Department of Community Medicine, JNMCH A.M.U. Data was analysed using IBM SPSS 20.0. Proportion, frequencies, chi square were used to interpret the data. Results: Among total females interviewed 201 (40.2%) were found to have symptoms of Reproductive Tract Infections, out of them 165, (74.1%) sought treatment. Among 165 females who started treatment, 62.4 % of females seeking treatment were literate.69% females who delayed treatment were illiterate. Self-motivation for treatment was seen among 60.2 % of literate females. Area of residence, social class and female's role in decision making also determined the treatment seeking behaviour. Conclusion: In our study female literacy has been found as major factor influencing the health seeking behaviour. Factors like place of residence, socio economic status, female role in decision making were significant. There is no denying the significant health benefits of supporting women's education. Education has a crucial role in family planning, from the earliest stages to caring for one's own health and newborn children.